Is There Any Correlation between Anti-Ro 52 Antibody Level with HematologicalAbnormalities in Systemic Lupus Erythematosus? - Amaylia Oehadian (Indonesian Journal of Rheumatology, 2022)
Background: Systemic lupus erythematosus (SLE) is a complexautoimmune disease with various clinical and serological manifestations.Previous studies have shown conflicting results about the association of antiRo 52 autoantibodies with hematological abnormalities in SLE. Weinvestigated the correlation between anti Ro 52 autoantibody with anemia,leucopenia, and thrombocytopenia in patients with SLE. Methods: Sixty-twobio archives serum of an SLE patient at the Division of Rheumatology,Department of Internal Medicine, Hasan Sadikin General Hospital,Bandung, Indonesia from 2017 to 2019 were enrolled in the study. Anti-Ro52 levels were examined using the ELISA method. The clinical data,treatment, and hematology paparametersere were analyzed retrospectively.Results: Among 62 bio-archive serum, four subjects were excluded becauseof incomplete data. Fifty-eight patients, all females were enrolled. Weidentified 57 (98.3%) subjects corticosteroid, 31 (53.4%) azathioprine and 28(48.3%) chloroquine. A correlation coefficient of anti-Ro 52 levels andhemoglobin, leukocyte and platelets were -0.037 (p = 0.391), 0.065 (p =0.315) and 0.092 (p = 0.246), respectively. Conclusion: No correlation wasfound between anti Ro 52 antibody levels with haematological abnormalitiesin patients with SLE. Further studies need to evaluate whether otherantibodies play important role in haematological abnormalities in SLE.